Factors affecting the outcomes of tibiotalocalcaneal fusion. (March 2020) - Pitts, Charles; Alexander, Bradley; Washington, Joshua; Barranco, Hannah; Patel, Romil; McGwin, Gerald; Shah, Ashish B.
Abstract : Aims: Tibiotalocalcaneal (TTC) fusion is used to treat a variety of conditions affecting the ankle and subtalar joint, including osteoarthritis (OA), Charcot arthropathy, avascular necrosis (AVN) of the talus, failed total ankle arthroplasty, and severe deformity. The prevalence of postoperative complications remains high due to the complexity of hindfoot disease seen in these patients. The aim of this study was to analyze the relationship between preoperative conditions and postoperative complications in order to predict the outcome following primary TTC fusion. Methods: We retrospectively reviewed the medical records of 101 patients who underwent TTC fusion at the same institution between 2011 and 2019. Risk ratios (RRs) associated with age, sex, diabetes, cardiovascular disease, smoking, preoperative ankle deformity, and the use of bone graft during surgery were related to the postoperative complications. We determined from these data which pre- and perioperative factors significantly affected the outcome. Results: Out of the 101 patients included in the study, 29 (28.7%) had nonunion, five (4.9%) required below-knee amputation (BKA), 40 (39.6%) returned to the operating theatre, 16 (15.8%) had hardware failure, and 22 (21.8%) had a postoperative infection. Patients with a preoperative diagnosis of Charcot arthropathy and non-traumatic OA had significantly higher nonunion rates of 44.4% (12 patients) and 39.1% (18 patients) (p = 0.016) and infection rates of 29.6% (eight patients) and 37% (17 patients) compared to patients with traumatic arthritis, respectively (p = 0.002). There was a significantly increased rate of nonunion in diabetic patients (RR 2.22; p = 0.010). Patients with chronic kidney disease were 2.37-times more likely to have a nonunion (p = 0.006). Patients aged over 60 years had more than a three-fold increase in the rate of postoperative infection (RR 3.60; p = 0.006). The use of bone graft appeared to be significantly protective against postoperative infection (p = 0.019). Conclusion: We were able to confirm, in the largest series of TTC ankle fusions currently in the literature, that there remains a high rate of complications following this procedure. We found that patients with a Charcot or non-traumatic arthropathy had an increased risk of nonunion and postoperative infection compared to individuals with traumatic arthritis. Those with diabetes, chronic kidney disease, or aged over 60 years had an increased risk of nonunion. These findings help to confirm those of previous studies. Additionally, our study adds to the literature by showing that autologous bone graft may help in decreasing infection rates. These data can be useful to surgeons and patients when considering, discussing and planning TTC fusion. It helps surgeons further understand which patients are at a higher risk for postoperative complications when undergoing TTC fusion. Cite this article: Bone Joint J . 2020;102-B(3):345–351.